The Influence of Health Promotion Through Media on Students' Knowledge About TB Disease in State Middle Schools in Makassar City - Musiana, Musiana; Andiani, Andiani (International Journal of Health Sciences, 2023)
TB treatment is a long-term type of treatment. Usually the duration of treatment can last 3-9 months. During treatment, sufferers must be diligent and disciplined in taking medication and regularly check with the doctor to ensure the progress of treatment until the sufferer recovers completely. The aim of this research is to determine the effect of health promotion through the media on students' knowledge about TB disease in Makassar City State Middle Schools in 2020. The type of research used was a quasi experimental study with a pretest posttest group with control design where the sample members in the intervention and control groups were carried out using purposive sampling, the sample size was 70 students with 35 students in each group. Results: There were differences in knowledge about TB disease in students before and after being given health promotion in both the intervention group (p= 0.000) and the control group (p= 0.036). Health promotion through the media gave higher results, namely 50.33 compared to leaflet media 28.67 with a knowledge difference of 21.66. Conclusion: The results of the study show that media is more influential than leaflet media on students' knowledge about TB disease in Makassar City State Middle Schools.